2016
DOI: 10.1186/s12864-016-2922-9
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of cis-acting loci leading to differential allele expression in F1 mice and their relationship to loci harboring genes affecting complex traits

Abstract: BackgroundGenome-wide surveys have detected cis-acting quantitative trait loci altering levels of RNA transcripts (RNA-eQTLs) by associating SNV alleles to transcript levels. However, the sensitivity and specificity of detection of cis- expression quantitative trait loci (eQTLs) by genetic approaches, reliant as it is on measurements of transcript levels in recombinant inbred strains or offspring from arranged crosses, is unknown, as is their relationship to QTL’s for complex phenotypes.ResultsWe used transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…These studies demonstrated relatively lower Gabra2 transcript and protein levels in the B6 and F1 seizure susceptible strains compared to the 129 protective background strain. This strain dependence of expression of GABA receptor subunits is consistent with previous reports (Korostynski et al 2006;Mulligan et al 2012;Yeo et al 2016). Moreover, the administration of the 1,5-BDZ clobazam (CLB) is associated with a higher temperature threshold for hyperthermia-induced seizures in F1.Scn1a +/− mice, which indicates that potentiating GABA A receptors has a strong anti-seizure effect in these mice .…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…These studies demonstrated relatively lower Gabra2 transcript and protein levels in the B6 and F1 seizure susceptible strains compared to the 129 protective background strain. This strain dependence of expression of GABA receptor subunits is consistent with previous reports (Korostynski et al 2006;Mulligan et al 2012;Yeo et al 2016). Moreover, the administration of the 1,5-BDZ clobazam (CLB) is associated with a higher temperature threshold for hyperthermia-induced seizures in F1.Scn1a +/− mice, which indicates that potentiating GABA A receptors has a strong anti-seizure effect in these mice .…”
Section: Introductionsupporting
confidence: 91%
“…We and others have previously reported that there is marked strain dependence in the expression levels of the α 2 subunit of GABA A receptors (Mulligan et al 2012;Yeo et al 2016). This strain dependent expression difference is correlated with phenotype severity in the DS mouse model, suggesting that it may contribute to the underlying protection from seizures in 129.Scn1a +/− mice .…”
Section: The Magnitude Of Azd7325 Effect Is Dependent Upon the Backgrmentioning
confidence: 71%
See 2 more Smart Citations
“…Strategies such as assessing behavior in a panel of recombinant inbred strains, such as the B6 by D2 cross (BXD RI), allow for genetic mapping of quantitative trait loci (QTLs) or chromosomal regions that may contain genes that influence susceptibility or resistance to THC-related behaviors (Plomin et al, 1991; Williams & Williams, 2017). Newer techniques in RNA and chromatin sequencing also make it possible to identify epigenetic alterations following THC treatment (Scott-Boyer & Deschepper, 2013; Goldowitz et al, 2014; Yeo et al, 2016). These preclinical advances are critical in identifying translational biomarkers of risk and consequences of drug use in human populations (Crabbe, 2016).…”
Section: Discussionmentioning
confidence: 99%